On the detection of carbon fibre storage contamination and its effect on the fibre–matrix interface. Issue 1 (December 2018) - Li, Quanxiang; Woodhead, Andrea; Church, Jeffrey; Naebe, Minoo
Abstract Contamination caused by inappropriate carbon fibre (CF) storage may have an impact on their end use in reinforced composite materials. Due to the chemical complexity of CFs it is not easy to detect potential contaminants, especially at the early stage during manufacturing and handling. In this paper, X-ray Photoelectron Spectroscopy (XPS), Fourier Transform Infrared (FTIR) spectroscopy and Surface Energy Analysis (IGC-SEA) were used to assess the surfaces of CFs stored in polyolefin zip-lock bags for possible contamination. Only after over 2 months in-bag storage, was XPS capable of detecting a minor increase in nitrogen on the CF surface while FTIR revealed the presence of fatty acid amides and fatty acids, both associated with the storage media. However neither of these techniques were sensitive enough to show significant evolution of the amount of contamination as a function of storage time. In contrast, IGC-SEA distinguished surface energy differences between CFs before and after storage. These differences were found to change as a function of storage time, which were attributed to increases in contamination amounts. Single fibre fragmentation tests indicated that the surface contamination had potential to disrupt the fibre-matrix interface. These findings provide a new method for assessing the surface contamination of CFs with potential application to other materials.